Associations between dysbiosis gut microbiota and changes of neurotransmitters and short-chain fatty acids in valproic acid model rats - Zhong, Jiu-Gen; Lan, Wan-Ting; Feng, Yan-Qing; Li, Yin-Hua; Shen, Ying-Ying; Gong, Jia-Heng; Zou, Zhi; Hou, Xiaohui (Frontiers in Physiology, 2023)
The microbiota-gut-brain axis plays an important role in the pathophysiology of autism spectrum disorder, but its specific mechanisms remain unclear. This study aimed to explore the associations of changes in neurotransmitters and short-chain fatty acids with alterations in gut microbiota in valproic acid rats. Here, the autism model rats were established by prenatal exposure to valproic acid (VPA). The Morris water maze test, open field test and three-chamber test were conducted to assess the behaviors of rats. 16S rRNA gene sequences extracted from fecal samples were used to assess the gut microbial composition. Gas and liquid chromatography-mass spectroscopy was used to identify short-chain fatty acids in fecal samples and neurotransmitters in the prefrontal cortex, respectively. The results showed that 28 bacteria taxa between valproic acid rats and control rats were identified and the most differential bacteria taxa in valproic acid rats and control rats belonged to species metagenome and Lactobacillus intestinalis. Acetic acid, butyric acid, valeric acid, isobutyric acid and isovaleric acid were significantly decreased in the valproic acid rats compared to control rats. Five transmitters (threonine, kynurenine, tryptophan, 5-hydroxyindoleacetic acid, denoted as 5-HIAA, and betaine aldehyde chloride, denoted as BAC) were significantly decreased, whereas betaine was increased in the prefrontal cortex of valproic acid rats compared to control rats. A variety of neurotransmitters (≥4) were correlated with Pseudomonas spp、Collisella spp and Streptococcus spp at the genus level, and they were also related to the decrease of short-chain fatty acids. These results provide microbial and SCFAs frameworks for understanding the role of the microbiota-gut-brain axis in autism spectrum disorder and shed new light on autism spectrum disorder treatment.